RKKY interaction and intervalley processes in p-doped transition-metal dichalcogenides - Mastrogiuseppe, Diego Martín (2014)
We study the Ruderman-Kittel-Kasuya-Yosida interaction in p -doped transition-metal dichalcogenides such as MoS 2 and WS 2 . We consider magnetic impurities hybridized to the Mo d orbitals characteristic of the valence bands. Using the Matsubara Green's-function formalism, we obtain the two-impurity interaction vs their separation and chemical potential of the system, accounting for the important angular dependence which reflects the underlying triangular lattice symmetry. The inclusion of the valence-band valley at the Γ point results in a strong enhancement of the interaction. Electron-scattering processes transferring momentum between valleys at different symmetry points give rise to complex spatial oscillation patterns. Variable doping would allow the exploration of rather interesting behavior in the interaction of magnetic impurities on the surfaces of these materials, including the control of the interaction symmetry, which can be directly probed in scanning tunneling microscopy experiments